AKTIVASI GEN-Z TERHADAP PENGEMBANGAN UMKM MELALUI DIGITALISASI: Studi Kasus di Wilayah Kapanewon Moyudan - Ramdhani, Ahmad Thoriq Akhsan; Agung Rashif Madani (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economic growth, contributing significantly to the Gross Domestic Product (GDP) and employment. However, access to financial resources and markets remains a challenge for MSMEs, especially those operating in the Moyudan Subdistrict. This research aims to analyze the role of Generation Z in addressing these challenges through the digitalization of MSMEs. This study is a qualitative descriptive research that involves observations and the collection of primary and secondary data. The research findings reveal that Generation Z plays an innovative role in the development of MSMEs through digitalization. Through digital transformation, MSMEs can enhance their visibility and efficiency through e-commerce platforms and online promotions. This digital transformation is supported by the high internet penetration and social media usage in Indonesia. The government also plays a role in developing digital skills among Generation Z through various programs. Digitally savvy Generation Z individuals can actively contribute to the growth of MSMEs, as seen in the success of the "KKN Konversi" event in marketing Moyudan's MSME products. As seen in the results of this research, the role of Generation Z can be a hope for the progress of MSMEs in the Mayudan Subdistrict region.